Pemanfaatan daun Kersen (Muntinga calabura L) dalam pewarnaan bahan tekstil yang ramah lingkungan - Rosyida, Ainur; Wibowo, Danur Kusuma (Jurnal Rekayasa Proses, 2025)
Cherry leaves can be used as a textile dye due to their content of flavonoids and tannins that produce a yellow color on the cotton fabric. Improving dyeing results can be achieved by selecting the appropriate mordant type and mordanting method, as cherry leaves are classified as mordant dyes. This study aims to determine the effect of varying pre-mordanting times and dyeing times on the dyeing results of cotton fabric with cherry leaf extract. The dyeing process began with mordanting the fabric using Polyaluminium chloride (PAC) various times: 30, 45, 60 minutes, followed by drying. The fabric was then dyed at room temperature for varying times: 60, 90,120 minutes, followed by washing and drying. To assess dyeing quality, the fabric was tested for color strength (k/s), wash fastness, and rub fastness. Data analysis using two-way ANOVA showed that variations in pre-mordanting time and dyeing time did not significantly affect color strength, wash fastness, or rub fastness values. The dyeing results with 9 different processing conditions yielded yellow colors with varying k/s, ranging from: 4.43-5.57. The wash fastness test showed a fairly good average color change (GS: 3), and the color staining was good (SS:4-5). The dry rub fastness test showed very good average staining (SS:5), while the wet rub fastness also demonstrated good staining (SS:4-5). . The use of PAC mordant and pre-mordant methods are considered the right choice to improve dyeing results. The results indicate that cotton fabric dyed with cherry leaf extract, using pre-mordanting with PAC, without heating, and with a single dyeing process, can achieve good quality and can be applied in the textile industry/craft to produce quality and environmentally friendly products.